2020
DOI: 10.1111/ajd.13308
|View full text |Cite
|
Sign up to set email alerts
|

The association of anti‐gliadin and anti‐transglutaminase antibodies and chronic plaque psoriasis in Indian patients: Preliminary results of a descriptive cross‐sectional study

Abstract: Background: Gluten sensitivity among psoriasis patients and its association with gender, age, disease duration and severity of psoriasis are under studied in Indians. Objective: To examine association among serum levels of anti-tTG and anti-gliadin antibodies and clinical features including gender, age, duration and severity of psoriasis. Methods: Serum levels of anti-transglutaminase and anti-gliadin antibodies were measured quantitatively in 80 (M:F 57:23) psoriasis patients aged 15 to 83 years and matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Still, they found that celiac disease patients had the highest AGA-IgA levels, followed by psoriasis patients with moderate levels and healthy controls with only weak positive AGA-IgA levels [ 27 ]. Likewise, another study from India found no relationship between age, sex, the severity of psoriasis, and celiac antibody levels [ 28 ]. Moreover, there are studies suggesting that a gluten-free diet may be beneficial in celiac antibody-positive psoriasis patients, but additional, better-designed studies are needed to confirm this [ 29 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Still, they found that celiac disease patients had the highest AGA-IgA levels, followed by psoriasis patients with moderate levels and healthy controls with only weak positive AGA-IgA levels [ 27 ]. Likewise, another study from India found no relationship between age, sex, the severity of psoriasis, and celiac antibody levels [ 28 ]. Moreover, there are studies suggesting that a gluten-free diet may be beneficial in celiac antibody-positive psoriasis patients, but additional, better-designed studies are needed to confirm this [ 29 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A UK study found that patients with psoriasis have a higher prevalence of the disease. Studies in Italy, the Czech Republic, and India confirmed an increased prevalence of coeliac disease in psoriasis [127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. There are also isolated reports that do not confirm the association of psoriasis with coeliac disease or the presence of elevated celiac-specific antibodies, suggesting the need for further follow-up of patients [142,143].…”
Section: Coeliac Diseasementioning
confidence: 99%
“…Alehan et al 391 Balci et al 390 Gabrielli et al 274 Inaloo et al 392 Lahat et al 344 393 Khoshbaten et al 397 Nicoletti et al 394 Rodrigo et al 395 Roth et al 396 358 Choung et al 360 Gusso et al 398 Hujoel et al 290 Potter et al 357 Shahbazkhani et al 399 Shen et al 402 Stenson et al 400 Vanciková et al 401 404 De Bastiani et al 403 Montesu et al 406 Dhattarwal et al 405 Nagui et al 407 Singh et al 408 Care. This is an Open Access publication distributed under the terms of the Creative Commons Attribution CC BY 4.0 licence, which permits unrestricted use, distribution, reproduction and adaption in any medium and for any purpose provided that it is properly attributed.…”
Section: Referencementioning
confidence: 99%